Identifying pastoral and plant products in local and imported pottery in Early Bronze Age southeastern Arabia - Suryanarayan, Akshyeta; Méry, Sophie; Swerida, Jennifer; Esposti, Michele Degli; Dollarhide, Eli; Döpper, Stephanie; Douglas, Khaled A.; Eddisford, Daniel; Al-Jahwari, Nasser S.; Mazuy, Arnaud; Moraleda-Cibrián, Núria; Vreeze, Michel de; et al. (PLOS ONE, 2025)
The origins of ceramic technology in the Oman Peninsula have a unique history in the context of ancient West Asia. Local pottery production in northern Oman and the United Arab Emirates is not documented until the early to mid-third millennium BC during the Early Bronze Age. This period was characterised by increasing sedentism and the expansion of long-distance exchange networks that operated across the Persian Gulf between Arabia, Mesopotamia, Iran and South Asia, including the exchange of ceramic vessels. In order to explore the links between ceramic technology and type, subsistence practices and sedentism as ceramic production was adopted in the region, we analysed the lipid content of Early Bronze Age pottery (n = 179) in southeastern Arabia from inland and coastal sites. The ceramic assemblage examined includes pottery produced locally at the site level as well as vessels that are distributed regionally. The contents of imported pottery from Mesopotamia and the Indus Civilisation from inland and coastal sites were also studied to determine the organic products that may have been transported as part of long-distance exchange. The results reveal the presence of pastoral products, such as meat and dairy products, in some of the earliest vessels produced in southeastern Arabia, as well as imported Mesopotamian vessels. Plant products are detected in a small minority of vessels in locally-produced and imported vessels, such as Fine Red Omani vessels and Black-Slipped Jars from the Indus Civilisation. Such an investigation demonstrates the importance of using biomolecular methods to study dietary practices and vessel use in southeastern Arabia on a larger scale.